2018
DOI: 10.20546/ijcmas.2018.712.161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of N, P, K Levels and Plant Densities on Growth, Yield and Quality of Pointed Gourd (Trichosanthes dioica Roxb.)

Abstract: The present study pertains to the effect of N,P,K levels, plant densities and its interaction on growth, yield and quality of pointed gourd (Trichosanthes Dioica Roxb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
2
1
0
Order By: Relevance
“…Reducing sugar (3.34%) was maximum in the treatment T 5 (1.0 m × 2.0 m), which was statistically found at par with (3.24%) and (3.16%) by treatment T 4 (0.90 m × 2.0 m) and T 3 (0.75 m × 2.0 m).more reducing sugar was obtained from widely spaced than closely spaced plant due to better translocation and accumulation of nutrients. These results are in conformity with the findings of Siva et al (2018) [8] in pointed gourd. Maximum non reducing sugar (4.52%) was recorded in the treatment T 5 (1.0 m × 2.0 m), which was statistically found at par with (4.40%) and (4.28%) treatment T 4 (0.90 m × 2.0 m) and T 3 (0.75 m × 2.0 m).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Reducing sugar (3.34%) was maximum in the treatment T 5 (1.0 m × 2.0 m), which was statistically found at par with (3.24%) and (3.16%) by treatment T 4 (0.90 m × 2.0 m) and T 3 (0.75 m × 2.0 m).more reducing sugar was obtained from widely spaced than closely spaced plant due to better translocation and accumulation of nutrients. These results are in conformity with the findings of Siva et al (2018) [8] in pointed gourd. Maximum non reducing sugar (4.52%) was recorded in the treatment T 5 (1.0 m × 2.0 m), which was statistically found at par with (4.40%) and (4.28%) treatment T 4 (0.90 m × 2.0 m) and T 3 (0.75 m × 2.0 m).…”
Section: Resultssupporting
confidence: 94%
“…More total sugar (%) was obtained from widely spaced than closely spaced plant due to better translocation and accumulation of nutrients. These results are in conformity with the findings of Siva et al (2018) [8] in pointed gourd.…”
Section: Resultssupporting
confidence: 94%
“…(fruits) without hampering the yield potential of the crop". Siva et al, [8] reported that "150:60:60 NPK kg per ha + 1.5m x 1m spacing recorded maximum growth, yield and quality parameters viz., number of nodes per vine, number of primary branches per vine, number of fruits per vine, fruit length, fruit diameter, yield per vine, yield per plot, total yield, number of seeds per fruit, fruit retention percentage, ascorbic acid content, protein content and total soluble solids and the minimum values were recorded for the parameters node at which first male flower appeared, node at which first female flower appeared, days taken to first harvest and days taken from fruit set to marketable maturity. However, the application 175:70:70 NPK Kg per ha + 1.5m x 1.5m spacing recorded maximum main vine length and internodal length whereas 125:50:50 NPK Kg per ha + 1.5m x 1m spacing recorded minimum days taken for opening of first male flower and days taken for opening of first female flower.…”
Section: Pointed Gourdmentioning
confidence: 99%